Firm Value and Sustainability Assessment of Food and Agriculture Systems - Septian, Septian; Anuar, Nik Arieff Ashaff Bin Nik; Suarsa, Abin (Journal of Accounting Science, 2025)
General Background: Sustainability has become a key focus in the global business sector, requiring companies to address social and environmental impacts alongside financial performance. Indonesia's plantation sector plays a critical role in the national economy, yet the adoption of sustainability standards and its relationship with stock value remains under-explored. Specific Background: While previous studies often utilise a generalised or partial approach to sustainability, the FAO's Sustainability Assessment of Food and Agriculture Systems (SAFA) framework offers a more comprehensive evaluation. This study investigates the relationship between the economic dimensions of SAFA and the stock value of plantation companies listed on the IDX over the period 2022-2023. Knowledge Gaps: Research linking SAFA implementation specifically to stock value in the plantation sector is limited, and previous findings are inconsistent. Objective: To provide empirical evidence that addresses these inconsistencies by assessing the effect of the economic dimensions of SAFA on stock value. Methods: A mixed approach with quantitative analysis using Generalised Estimating Equation (GEE) was applied to data on plantation companies listed on the IDX. Results: None of the four economic dimensions-Investment, Vulnerability, Product & Information Quality, and Local Economy-showed a significant effect on stock value. Novelty: This is the first study to explicitly test SAFA in the context of the Indonesian capital market. Implications: The findings suggest that investors may not fully consider sustainability disclosures in investment decisions, highlighting the need for greater awareness and education.